2010
DOI: 10.1159/000319362
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene Polymorphism Associated with Short-Term Treatment Response to Venlafaxine

Abstract: Background: Polymorphisms of serotonin transporter, especially serotonin transporter linked promoter region (5- HTTLPR) and serotonin transporter intron 2 variable number tandem repeat (5-HTTVNTR), have been suggested to be associated with treatment response to selective serotonin reuptake inhibitors. However, there have been only few reports of the association between 5-HTTLPR or 5-HTTVNTR and treatment response to venlafaxine. Methods: 84 Korean major depressive disorder patients were included in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 75 publications
3
8
0
Order By: Relevance
“…However this was in contrast to the finding by Proft et al [4], which showed a significant association between SLC6A4 genotype (l A l A ) and poor response to venlafaxine. Our results are however in alignment with another prospective study [11] involving 84 Korean MDD patients given a titrated daily dose of 75-150 mg of venlafaxineXR for 4 weeks. That study revealed that 5-HTTLPR L/L and L/S genotype patients had MADRS and HAM-A score reductions significantly greater than those patients with an S/S genotype.…”
supporting
confidence: 87%
“…However this was in contrast to the finding by Proft et al [4], which showed a significant association between SLC6A4 genotype (l A l A ) and poor response to venlafaxine. Our results are however in alignment with another prospective study [11] involving 84 Korean MDD patients given a titrated daily dose of 75-150 mg of venlafaxineXR for 4 weeks. That study revealed that 5-HTTLPR L/L and L/S genotype patients had MADRS and HAM-A score reductions significantly greater than those patients with an S/S genotype.…”
supporting
confidence: 87%
“…Meta‐analytic results further suggested an opposite effect of the variant in Caucasians versus Asians, but results remained contradictory with evidence of high heterogeneity among studies [Kato and Serretti, ]. Similarly, no association was found between STin2 and antidepressant induced side effects [Takahashi et al, ; Popp et al, ; Smits et al, ; Higuchi et al, ; Wilkie et al, ; Lee et al, ] (Supplementary Table I), and a meta‐analysis confirmed the result [Kato and Serretti, ].…”
Section: Monoaminergic Systemmentioning
confidence: 79%
“…Available studies mainly suggested the S allele as risk factor [Perlis et al, ; Murphy et al, ; Popp et al, ; Hu et al, ; Smits et al, ; Maron et al, ], while only one study found an opposite result for sexual dysfunction in females taking oral contraceptives [Bishop et al, ]. On the other hand, studies reporting no association between 5‐HTTLPR and antidepressant side effects were mainly performed in non‐Caucasian samples [Takahashi et al, ; Ng et al, ; Hougardy et al, ; Higuchi et al, ; Lee et al, ; Strohmaier et al, ], further suggesting a population‐specific effect of the polymorphism (Supplementary Table I). Some recent findings made the picture even more complex: (i) rs25531 may lay within the 5‐HTTLPR sequence and influence the functional effect of 5‐HTTLPR itself [Hu et al, ]; and (ii) novel even if rare 5‐HTTLPR alleles were identified (17, 18. and 11 repeats) [Ehli et al, ].…”
Section: Monoaminergic Systemmentioning
confidence: 99%
“…These inconsistent results from the only 2 available studies controlling for serum levels on the other hand are in line with the ambiguous picture provided by the numerous studies not controlling for serum levels. Studies showing a better response to antidepressants in patients with the l-allele [14][15][16][29][30][31] are balanced by studies showing no effect of the genotype [26,[32][33][34] or a worse response in patients with the l-allele [35,36]. However, as it is the case in our study and the study by Dreimüller et al in all these studies different antidepressants, time points, outcome parameters and genotype definitions were used rendering a comparison nearly impossible.…”
mentioning
confidence: 61%